Heterostructural design of I-deficient BiOI for photocatalytic decoloration and catalytic CO2 conversion. Issue 14 (27th June 2019) - Hu, Chechia; Huang, Hui-Xin; Lin, Yi-Feng; Tung, Kuo-Lun; Chen, Tzu-Hsin; Lo, Lin
Abstract : I − vacancies in BiOI play a major role in governing the photocatalysis and catalysis. Abstract : In this study, I-deficient BiOI is subjected to heterostructural design by coupling with SrTiO3 (BiOI/SrTiO3, BS) or modification with (3-aminopropyl)trimethoxysilane (APTMS) to enhance the photocatalytic and catalytic activity, respectively. X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), and elemental analyses demonstrated the presence of I − vacancies in BiOI, which acted as electron traps in the photocatalytic reaction, and the absence of Lewis basic sites in the catalytic CO2 reaction to limit the conversion efficiency. After modification, the BS composite exhibited high activity for photocatalytic methyl orange decoloration under visible light irradiation because of facile charge separation resulting from the I − vacancies of BiOI and the intimate heterojunction at the BiOI/SrTiO3 interface. On the other hand, modification of BiOI with APTMS could greatly strengthen the Lewis basicity to enhance the catalytic CO2 -to-polycarbonate (PC) conversion activity. In summary, I − vacancies play a vital role in determining the activity of I-deficient BiOI both in photocatalysis and catalysis. Hence, I-deficient BiOI would be a facile catalyst and upon a certain degree of modification, may find promising applications in photocatalysis and catalysis for CO2 conversion and environmental remediation.